Increasing Teacher Performance Through Strengthening Transformational Leadership, Personality, and Work Motivation - Mokodompit, Rosnany; Setyaningsih, Sri; Suhendra (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
This research aims to increase teacher performance and analyze the influence of transformational leadership variables, personality, and work motivation on the performance of private kindergarten teachers accredited "B". variables contained in the quantitative research stage. This research uses the path analysis method to determine the influence between the variables studied and the SITOREM method for indicator analysis to determine the influence of variables who have non-PNS status and are certified educators. The sample resulted in 173 teacher respondents. The sampling technique in this research used simple random sampling. The results of research using the SITOREM path analysis method show that there is a direct positive influence between transformational leadership on teacher performance; There is a direct positive influence between personality on teacher performance; There is a direct influence between work motivation and teacher performance; There is no direct positive influence between Transformational Leadership on Work Motivation; There is no direct positive influence between Personality and Work Motivation; There is no direct positive influence between Transformational Leadership on Personality; There is no indirect positive influence between transformational leadership on teacher performance through work motivation; There is no indirect influence between Personality on Teacher Performance (Y) through Work Motivation. The results of the SITOREM analysis obtained optimal solutions from 23 indicators, 5 indicators were still weak so they needed to be improved and 18 indicators were good so they were maintained or developed. Improvements to indicators that are still weak are also given the following order of priority for handling: Conscientiousness – responsible, reliable, diligent; Salary/Pay; Instructional support – stronger influence of ethical/moral values of followers; Compensation; Productivity.